Hubungan green perceived value, green brand image, dan green trust terhadap green purchase intention - Rakhmawati, Dewi; Puspaningrum, Astrid; Hadiwidjojo, Djumilah (Fakultas Ekonomi, UIN Maliki Malang, 2019)
The issue of environmental damage caused by industry continues to increase every year accompanied by real conditions that occur, either damage on humans, animals, plants, and the environment. Nowadays people are increasingly aware of the importance of preserving the environment more selectively in the selection of products used. This study was conducted to determine the effect of green perceived value and green brand image on green purchase intention on consumers of Malang Bodyshop. The number of samples study were 141 respondents of The Bodyshop customers in Malang. This study uses a purposive sampling technique with the following criteria: (1) At least 18 years old (2) Domiciled in the city of Malang and once made a purchase at the outlets of The Bodyshop Malang (3) Have used The Bodyshop products at least more than once. Data analysis techniques are performed using Partial Least Square (PLS). The result of the study shows that it turns outs that trust in green products plays a very important role in the desire of consumers to buy. The result obtained by green trust fully mediate green perceived value and green brand image of the green purchase intention. There is a positive relationship between the green perceived value on green trust and green brand image of green trust. It was also found in this study that there was a negative relationship between the green perceived value on green purchase intention and the negative relationship between the green brand image of the green purchase intention.Â